2022
DOI: 10.3390/cells11040741
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Viral Protein HBx and the Molecular Mechanisms Modulating the Hallmarks of Hepatocellular Carcinoma: A Comprehensive Review

Abstract: With 296 million cases estimated worldwide, chronic hepatitis B virus (HBV) infection is the most common risk factor for hepatocellular carcinoma (HCC). HBV-encoded oncogene X protein (HBx), a key multifunctional regulatory protein, drives viral replication and interferes with several cellular signalling pathways that drive virus-associated hepatocarcinogenesis. This review article provides a comprehensive overview of the role of HBx in modulating the various hallmarks of HCC by supporting tumour initiation, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 168 publications
(171 reference statements)
0
35
0
1
Order By: Relevance
“…This suggests that CLD promotes the integration of HBx-encoding HBV DNA ( Figure 2 ), and sustained high levels of HBx could act as a complete carcinogen [ 61 ]. Thus, HBx promotes the development of cancer hallmarks [ 62 ]. None of these HBx transgenic mice developed HCC on a background of cirrhosis.…”
Section: Role Of Hbx In the Immunopathogenesis Of Cld And Hccmentioning
confidence: 99%
“…This suggests that CLD promotes the integration of HBx-encoding HBV DNA ( Figure 2 ), and sustained high levels of HBx could act as a complete carcinogen [ 61 ]. Thus, HBx promotes the development of cancer hallmarks [ 62 ]. None of these HBx transgenic mice developed HCC on a background of cirrhosis.…”
Section: Role Of Hbx In the Immunopathogenesis Of Cld And Hccmentioning
confidence: 99%
“…Moreover, HBx also regulates the cccDNA transcriptional activity by preventing transcriptional repressor recruitment on the cccDNA, including SIRT1 and HDAC1 [ 11 , 12 ]. HBx not only contributes to persistent HBV infection but also modulates several cell-signaling pathways, such as P53, mitogen-activated protein kinase (MAPK), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB), and the Janus kinase signal transducer and activator of transcription (JAK-STAT) pathways, thereby promoting cell proliferation and inducing carcinoma formation [ 13 , 14 , 15 , 16 ]. Anti-HBx could be a potential antivirus strategy for HBV infection, but because HBx is an intracellular protein and most antibodies against HBx are not sensitive enough, the discovery of inhibitors of HBx would be facilitated by the ability to screen large chemical libraries in a short time for molecular compounds against HBx.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we selected HBx as the target of siRNA silencing. HBx plays a critical role in HBV replication by binding with the nuclear cccDNA mini chromosome to initiate and maintain viral transcription [ 12 ]. Furthermore, a previous report demonstrated that inhibiting HBx using an NQO1 inhibitor could block cccDNA transcription [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IL-12 can promote macrophages to differentiate into the M1 phenotype [29]. However, the detailed mechanism of inhibition of HBV replication by IL- 12 is not yet understood well enough.…”
Section: Introductionmentioning
confidence: 99%